Environmental quality, international trade and economic growth: The case of Malaysia - Sadat, Ssekibaala Daaki; Alom, Md. Fardous (Inderscience Enterprises Ltd., 2016)
This paper examines the dynamic relationships between environmental quality, international trade and economic growth using annual data over the period of 1970-2011 for Malaysia. As such, we use GDP per capita and the square of GDP which we refer to as the scale and technique effect respectively, trade openness, energy consumption, composition effect and comparative advantage and CO2 emissions is the environmental quality indicator. We employ autoregressive distributed lag (ARDL) bounds testing approach to examine long-run association as well as the quantile regression (QREG) approach to examine how the relationship at different conditional distributions of CO2 emissions. ARDL results confirm the presence of long-run relationship. The scale effects are positive while technique effects are negative confirming the existence of an inverted U-shaped curve that provides evidence for environmental Kuznets curve (EKC) hypothesis for Malaysia. The turning point is estimated at around RM 27901.54 per capita. QREG results find the effect of CO2 emissions significant in the 90th percentile and the turning point is estimated around RM 28189.9 which is slightly higher than the one estimated for ARDL. Trade and composition effects reduce CO2 emissions which improves environmental quality while energy and comparative advantage increase CO2 emissions worsening environmental quality. This study provides a more comprehensive analysis and the robust findings may provide a basis for policy makers in designing environmentally sustainable trade and economic policies.